On Teaching the History of Nineteenth-Century Music - Frisch, Walter (Current Musicology, 2019)
This essay is adapted from the author’s “Reflections on Teaching Nineteenth-Century Music,” in The Norton Guide to Teaching Music History, ed. C. Matthew Balensuela (New York: W. W Norton, 2019).